Pre-chamber ignition systems: A methodological proposal to reproduce a reference case in a simplified experimental facility for fundamental studies. (November 2021) - Desantes, José M; López, J Javier; Novella, Ricardo; Antolini, Jácson
To further understand the processes and phenomena taking place in the pre-chamber (PC) ignition concept, many studies under simplified conditions have been carried out in different experimental facilities (e.g. constant volume chambers and rapid compression machines). However limited information is provided about how the volume, orifice diameter and number of orifices were defined, raising the question whether the results are representative of engine-like conditions or not. This novel study arises from the necessity to determine a methodology to reproduce a reference pre-chamber, preserving as much as possible its jet characteristics. A theoretical development based on the first law of thermodynamics has been performed, and a relationship between the effective flow area, pre-chamber volume and engine speed is proposed as the governing parameter of the mass exchange between chambers. Besides, relaying on the know-how of gas jets, a relationship between the orifice diameter, jet tip penetration and engine speed is suggested as the criterion to preserve the relative jet penetration (respect to the distance from the PC hole to the combustion chamber walls). A numerical validation of these assumptions was carried out using a one-dimensional flow calculator to estimate the thermodynamic properties and mass transfer between chambers, and a one-dimensional spray model to estimate the penetration of the PC combustion products jets. Finally, preserving the ratio between the total area of the PC holes and the product of the PC volume and the engine speed for two pre-chamber geometries, an identical pressure rise rate, in an angular basis, is achieved in both pre-chambers. Furthermore, the same relative jet penetration rate, in an angular basis, can be also achieved, even under different engine speeds, when the ratio between the orifice diameter and the product of the square of the jet free length and the engine speed is preserved.